2019
DOI: 10.1002/pon.5247
|View full text |Cite
|
Sign up to set email alerts
|

Digital divide and Internet health information seeking among cancer survivors: A trend analysis from 2011 to 2017

Abstract: Objective: The current study aims to explore the trend of Internet health information seeking (IHIS) in cancer survivors and the relationship between four dimensions of digital divide (eg, mental access, material access, skills access, and usage access) and IHIS.Methods: Data from three iterations (2011, 2013, and 2017) of Health Information National Trends Survey were analyzed. Only cancer survivors (2011: n=563; 2013: n=459; 2017: n=504) were included. ANOVA and multivariate regressions were performed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Results of the internet search influenced choice of treatment, choice of doctor, and enrollment in clinical trials [ 43 ]. A recent study examining IHIS (i.e., having looked for medical information on the internet for oneself or someone else in the past 12 months) in cancer survivors using data from the 2011, 2013, and 2017 iterations of HINTS [ 19 ] reported a rising trend for IHIS from 53.5% in 2011 to 69.2% in 2017 mirroring the trends in the general US population [ 44 ]. Despite an increase in the proportion of cancer survivors engaging in IHIS, the study confirmed a digital divide and further examined the dimensions of the digital divide: mental access (trust in online information and self-efficacy in health information seeking), material access (ease of internet access), skill access (skill to seek information online), and usage access (online health-related activities like emailing doctors and buying medicines).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the internet search influenced choice of treatment, choice of doctor, and enrollment in clinical trials [ 43 ]. A recent study examining IHIS (i.e., having looked for medical information on the internet for oneself or someone else in the past 12 months) in cancer survivors using data from the 2011, 2013, and 2017 iterations of HINTS [ 19 ] reported a rising trend for IHIS from 53.5% in 2011 to 69.2% in 2017 mirroring the trends in the general US population [ 44 ]. Despite an increase in the proportion of cancer survivors engaging in IHIS, the study confirmed a digital divide and further examined the dimensions of the digital divide: mental access (trust in online information and self-efficacy in health information seeking), material access (ease of internet access), skill access (skill to seek information online), and usage access (online health-related activities like emailing doctors and buying medicines).…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increase in the proportion of cancer survivors engaging in IHIS, the study confirmed a digital divide and further examined the dimensions of the digital divide: mental access (trust in online information and self-efficacy in health information seeking), material access (ease of internet access), skill access (skill to seek information online), and usage access (online health-related activities like emailing doctors and buying medicines). There was a significant positive association between IHIS and material access, usage access, and mental access (trust in online information) across all 3 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were surprised to find that survivors who lacked Internet access (and therefore completed assessments by mail) were over twice as likely to report PRO impairments even after adjusting for age, current cGVHD burden, and other socioeconomic variables. Previous studies have identified age, race, income, and educational level as factors associated with lower Internet usage among cancer survivors [66,67]. To our knowledge, this is the first study associating a lack of Internet access with worsened PROs among HCT survivors even after adjusting for these related demographic and socioeconomic variables.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, cancer is one of the health‐related words most searched for on the web. Many patients diagnosed with cancer and their families search online for diagnostic, prognostic, and treatment information . However, use of digital tools by cancer patients is not ubiquitous and is lower among several sub‐populations, including older individuals and those with environmental constraints (eg, lack of resources and other access barriers).…”
mentioning
confidence: 99%